1990
DOI: 10.1093/infdis/162.6.1341
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Diagnosis of Legionella Pneumonia: A 3-Year Prospective Study with Emphasis on Application of Urinary Antigen Detection

Abstract: During a 3-year period the frequency of legionellosis in hospitalized patients with community-acquired and nosocomial pneumonias was 3.4% (23/684 cases) and 5.9% (33/559), respectively. Of the diagnostic tests evaluated, detection of Legionella pneumophila serogroup 1 antigen in urine had the highest sensitivity, with 86% of culture-proven cases being positive. Sensitivities of serologic tests and examination of respiratory secretions (culture and direct immunofluorescence) were 36% and 26%, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
2
4

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 37 publications
1
45
2
4
Order By: Relevance
“…Currently, there are several commercially available tests (the Binax Legionella urinary antigen enzyme immunoassay [EIA], the Biotest Legionella urine antigen EIA, and the Binax NOW Legionella urinary antigen immunochromatographic test [ICT]) for the detection of L. pneumophila antigen in urine. All of these tests have been previously evaluated, confirming their utility for the diagnosis of Legionnaires' disease (6,12). A wider range of sensitivity has been reported, however, although no research has demonstrated significant differences in sensitivity between these tests.…”
mentioning
confidence: 79%
“…Currently, there are several commercially available tests (the Binax Legionella urinary antigen enzyme immunoassay [EIA], the Biotest Legionella urine antigen EIA, and the Binax NOW Legionella urinary antigen immunochromatographic test [ICT]) for the detection of L. pneumophila antigen in urine. All of these tests have been previously evaluated, confirming their utility for the diagnosis of Legionnaires' disease (6,12). A wider range of sensitivity has been reported, however, although no research has demonstrated significant differences in sensitivity between these tests.…”
mentioning
confidence: 79%
“…These data emphasise the high speci®city of Legionella urinary antigen assays that was found with the Binax and Biotest EIA [9,18]. Published sensitivity data for Legionella urinary antigen assays have so far related only to cultureproven cases in general and have not discriminated between serogroups or MAb subgroups [2,6,18,19]. This is largely due to the fact that infections caused by L. pneumophila serogroups 2±15 and some MAb subgroups of serogroup 1 occur only very rarely [12, 20±22].…”
Section: Detection Of Legionella Antigens In Urine Samples From Patiementioning
confidence: 99%
“…The outcome of patients with Legionnaires' disease depends on the speed with which a diagnosis can be established and the initiation of appropriate therapy [1,2]. Urinary antigen detection for the diagnosis of Legionnaires' disease has several advantages compared with other methods.…”
Section: Introductionmentioning
confidence: 99%
“…The reported sensitivities of both enzyme immunoassay (EIA) and immunochromatographic test (ICT) show great variation: 50 to 90% (3,7,8,19). These variations may be explained by differences in patient characteristics, the serogroup with which the patient is infected, the timing of collection the urine sample in the course of illness, and whether the urine is concentrated before testing.…”
mentioning
confidence: 99%